Family and Intimate Mobilities - Holdsworth, C. author. aut Link
X, 172 p.
Keywords: This book explores the many varied ways in which family and intimate lives are realized through mobility: from leaving home, courtship, relationship breakdown, moving house, commuting, family holidays through to children's mobilities, documenting how mobility creates, sustains and dissolves family and intimate relations.